ANALISIS ZAT GIZI DAN UJI DAYA TERIMA FLAKESTEPUNG PISANG BARANGAN MENTAH DAN TEPUNG TALAS - Vella Regalia; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Banana ‘barangan’ unripe flour and taro flour can be processed into flakes. Flakes is fast food favored all ages by children to the adults. Flakes has a unique shape. This research aims to determine the acceptability and nutritional content of flakes mixed of banana ‘barangan’ unripe and taro flour.The type of research was an experiment conducted by completely randomized design using three treatment, taro flour and banana ‘barangan’ unripe flour 2:1, 1:2, 1:1. Acceptability test of flakes banana ‘barangan’ unripe flour and taro flour by 30 student of faculty Public Health,University of North Sumatera, nutrient content analysis was tested in laboratory of Industrial Research and Standarization Agency Medan.The results of acceptability organoleptic test based on color, aroma, flavor and texture by 30 panelist showed the most preferred were flakes with of taro flour 25% and banana ‘barangan’ unripe flour 75%. The results of nutrient content analysis showed that three treatments had content carbohydrates 84,4%, 79,1%, 74,0%, content of protein 4,97%, 5,42%, 7,18% and fat 3,34%, 2,10%, 6,41%.It is recommended for people to take banana ‘barangan’ unripe flour and taro flour to become a flakes as alternative fast food to breakfast.Keywords: Banana ‘Barangan’ Unripe Flour, Taro Flour, Flakes, Acceptability, Nutrient Content